2014
DOI: 10.1177/0957650914539500
|View full text |Cite
|
Sign up to set email alerts
|

The effect of injector size on compressor performance in a transonic axial compressor with discrete tip injection

Abstract: The present study investigates the effects of injector size, which covers both circumferential extent and radial extent on compressor stability and radial work redistribution using time-accurate three-dimensional numerical simulations for multi-passages in a transonic compressor with discrete tip injection. Injector width ranges from 1% to 14.5% of casing perimeter and injector throat height varies from 2 to 6 times the height of rotor tip clearance. Six identical injectors are uniformly mounted around the ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Therefore, many active and passive control devices were used to control the impact of secondary flow. Active flow control techniques were widely exploited in high-load compressors, 2 such as boundary layer aspiration, 3 vortex generator jet, 4 tip injection, 5 and so on. On the other hand, passive flow control devices were developed by a contrasting idea, which can get rid of the constraint of external equipment to control the secondary flow of a compressor.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many active and passive control devices were used to control the impact of secondary flow. Active flow control techniques were widely exploited in high-load compressors, 2 such as boundary layer aspiration, 3 vortex generator jet, 4 tip injection, 5 and so on. On the other hand, passive flow control devices were developed by a contrasting idea, which can get rid of the constraint of external equipment to control the secondary flow of a compressor.…”
Section: Introductionmentioning
confidence: 99%
“…Nie et al 12 disclosed that a micro air injection using very small amount of air could improve the compressor stability by shifting the position of tip clearance vortex toward downstream without unloading the rotor tip. Beheshti et al 13 and Wang et al 14,15 found that tip injection reduced the TLF-related blockage, which was responsible for the stability enhancement of NASA Rotor 37. The latter built a relationship between the improvement in the stability and the decrement in the blockage.…”
Section: Introductionmentioning
confidence: 99%
“…The stabilizing effect of tip injection can be briefly summarized as the unloading effect, [7][8][9][10][11] the action on TLF or endwall blockage, [12][13][14][15][16][17] and the unsteady effect. [20][21][22][23][24] However, it is difficult to evaluate the influence on compressor efficiency accurately for the tip injection with external air source.…”
Section: Introductionmentioning
confidence: 99%
“…17,20,25,29 The injection velocity should be maximized by choking the injectors. 20,[23][24][25]32 Partly covering the annulus is adequate, although the optimal coverage is different for different compressors. 16,17,32,33 Nevertheless, the optimal options of some other parameters are still in dispute, such as injection yaw angle, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…20,[23][24][25]32 Partly covering the annulus is adequate, although the optimal coverage is different for different compressors. 16,17,32,33 Nevertheless, the optimal options of some other parameters are still in dispute, such as injection yaw angle, i.e. whether the jets should be injected axially (indicated or proved by Suder et al, 19 Strazisar et al, 20 and Weichert et al 28 ) or be made aligned with the blade camber line of rotor tip (supported by Hathaway, 21 Cassina et al, 23 and Khaleghi et al 25 ) is not determined.…”
Section: Introductionmentioning
confidence: 99%